Research Progress of Circular RNA CircHIPK3 in Non-small Cell Lung Cancer - Yuheng WANG; Liang CHEN (Chinese Journal of Lung Cancer)
Lung cancer ranks among the most prevalent and deadliest malignancies worldwide. Despite significant strides in targeted therapies and immunotherapy for lung cancer, curing the disease remains a highly prioritized issue. Circular RNAs (circRNAs), recently discovered RNA molecules characterized by covalently closed loop structures, possess features such as structural stability, sequence conservation, and disease-specific expression. Cutting-edge medical research has linked circRNA dysregulation to the progression of various cancers. Among these, circular RNA HIPK3 (circHIPK3), an oncogenic gene primarily derived from the second exon of the HIPK3 gene, has emerged as a focal point of investigation. Increasing evidences suggest that circHIPK3 is involved in the development of non-small cell lung cancer (NSCLC) and other malignancies. Aberrant expression of circHIPK3 is closely associated with the disease mechanisms, diagnosis, treatment, and prognosis of NSCLC. This review discusses the latest research advancements on circHIPK3 in NSCLC, aiming to promote precise diagnosis and treatment of lung cancer.